Upaya Peningkatan Literasi Keuangan pada Generasi Z Melalui Edukasi Finansial di MAN 2 Kampar - Nurbit Nurbit; Dzulhijjah Yetti; Yedi Sispurwanto; Hayatul Khairul Rahmat; Rahmad Akbar; Harmi Yelmi; Nurkholis Nurkholis (Indonesian Journal of Emerging Trends in Community Empowerment, 2026)
Financial literacy in Indonesia, particularly among Generation Z, remains low, with many students lacking an understanding of basic concepts such as budgeting, saving, investing, and managing debt. At MAN 2 Kampar, this issue is exacerbated by limited access to relevant financial information and a lack of practical skills in financial management. This condition causes students to struggle in making sound financial decisions, which may negatively impact their future. To address this problem, the proposed solution is to implement a comprehensive financial education program, including budgeting simulations, investment games, and real-life case studies. This program aims to provide hands-on experience for students, strengthen their understanding of financial management, and improve financial literacy so they can better face future financial challenges.